Projected 21st-century changes in marine heterotrophic bacteria under climate change - Kim, Heather H.; Laufkötter, Charlotte; Lovato, Tomas; Doney, Scott C.; Ducklow, Hugh W. (Frontiers in Microbiology, 2023)
Marine heterotrophic Bacteria (or referred to as bacteria) play an important role in the ocean carbon cycle by utilizing, respiring, and remineralizing organic carbon exported from the surface to deep ocean. Here we investigate the responses of bacteria to climate change using a three-dimensional coupled ocean biogeochemical model with explicit bacterial dynamics as part of the Coupled Model Intercomparison Project Phase 6. First, we assess the credibility of the century-scale projections (2015-2099) of bacterial carbon stock and rates in the upper 100 m layer using skill scores and compilations of the measurements for the contemporary period (1988-2011). Second, we demonstrate that across different climate scenarios, the simulated bacterial biomass trends (2076-2099) are sensitive to the regional trends in temperature and organic carbon stocks. Bacterial carbon biomass declines by 5-10% globally, while it increases by 3-5% in the Southern Ocean where semi-labile dissolved organic carbon (DOC) stocks are relatively low and particle-attached bacteria dominate. While a full analysis of drivers underpinning the simulated changes in all bacterial stock and rates is not possible due to data constraints, we investigate the mechanisms of the changes in DOC uptake rates of free-living bacteria using the first-order Taylor decomposition. The results demonstrate that the increase in semi-labile DOC stocks drives the increase in DOC uptake rates in the Southern Ocean, while the increase in temperature drives the increase in DOC uptake rates in the northern high and low latitudes. Our study provides a systematic analysis of bacteria at global scale and a critical step toward a better understanding of how bacteria affect the functioning of the biological carbon pump and partitioning of organic carbon pools between surface and deep layers.